Telemedicine Coverage of Intensive Care Units: A Narrative Review - Vranas, Kelly C. (Ann Am Thorac Soc, 2018)
Telemedicine coverage of intensive care units is an organizational innovation that has been touted as a means to improve access to and quality of critical care. The purpose of this narrative review is to discuss the different organizational models of intensive care unit telemedicine and factors that have influenced its adoption and to review the existing literature to consider whether it has lived up to its promise. We conclude by suggesting future directions to fill in some of the existing gaps in the literature.